Observational constraints on first-star Nucleosynthesis: II. spectroscopy of an ultra metal-poor CEMP-no star - Placco, Vinicius M.; Christlieb, Norbert (The astrophysical journal, 2016)
We report on the first high-resolution spectroscopic analysis of HE 0020-1741, a bright ( V = 12.9), ultra metal-poor ( ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn1.gif] $[\mathrmFe/\rmH]$ = −4.1), carbon-enhanced ( ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn2.gif] $[\rmC/\mathrmFe]$ = +1.7) star selected from the Hamburg/ESO Survey. This star exhibits low abundances of neutron-capture elements ( ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn3.gif] $[\mathrmBa/\mathrmFe]$ = −1.1) and an absolute carbon abundance A (C) = 6.1; based on either criterion, HE 0020-1741 is subclassified as a carbon-enhanced metal-poor star without enhancements in neutron-capture elements (CEMP-no). We show that the light-element abundance pattern of HE 0020-1741 is consistent with predicted yields from a massive ( M = ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn4.gif] $21.5\,M_ødot $ ), primordial-composition, supernova (SN) progenitor. We also compare the abundance patterns of other ultra metal-poor stars from the literature with available measures of C, N, Na, Mg, and Fe abundances with an extensive grid of SN models (covering the mass range ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn5.gif] $10\mbox-100\,M_ødot $ ), in order to probe the nature of their likely stellar progenitors. Our results suggest that at least two classes of progenitors are required at ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn6.gif] $[\mathrmFe/\rmH]$ ##IMG## [http://ej.iop.org/images/0004-637X/833/1/21/apjaa431dieqn7.gif] $\lt \,-4.0$ , as the abundance patterns for more than half of the sample studied in this work (7 out of 12 stars) cannot be easily reproduced by the predicted yields.
Gesehen am 12.10.2017